2014
DOI: 10.1261/rna.043372.113
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Hfq can replace Escherichia coli Hfq for most of its function

Abstract: A gene for the Hfq protein is present in the majority of sequenced bacterial genomes. Its characteristic hexameric ring-like core structure is formed by the highly conserved N-terminal regions. In contrast, the C-terminal forms an extension, which varies in length, lacks homology, and is predicted to be unstructured. In Gram-negative bacteria, Hfq facilitates the pairing of sRNAs with their mRNA target and thus affects gene expression, either positively or negatively, and modulates sRNA degradation. In Gram-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 88 publications
1
28
0
Order By: Relevance
“…We may hypothesize that a high level of hfq expression and some structural particularities of the Hfq protein, including the presence of a unique C-terminal domain (104), may explain these unique features. Hfq could control target gene expression either directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We may hypothesize that a high level of hfq expression and some structural particularities of the Hfq protein, including the presence of a unique C-terminal domain (104), may explain these unique features. Hfq could control target gene expression either directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…The CD1974 protein has an unusual C-terminal region. In E. coli, the full-length CD1974 protein is functional in sRNA-mediated regulation (55,104) and substitutes for most, but not all, of the traits of E. coli Hfq in phenotypic assays while the C-terminal domain contributes to RNA-binding efficiency of this RNA chaperone (104). The C. difficile hfq gene is flanked by the miaA gene (CD1975) encoding a tRNA ⌬ 2 -isopentenylpyrophosphate transferase and CD1973 encoding a putative pyridoxal phosphate-dependent transferase.…”
Section: Construction Of a Strain Depleted For Hfq And Analysis Of Itmentioning
confidence: 99%
“…Deletion of the C-terminal tail in E. coli Hfq also reduced in vitro binding affinity to the V. cholera Qrr sRNAs [35], and tryptophan quenching experiments showed the C-terminus can bind the hfq mRNA [18]. Interestingly, Hfq from Clostridium difficile , which has an extremely asparagine and glutamine-rich tail, can complement many of the functions of E. coli Hfq [36]. In this heterologous context, deletion of the tail impacted some of the regulation by C. difficile Hfq.…”
Section: Binding Of Srnas and Mrnasmentioning
confidence: 99%
“…By contrast, later studies found that the CTD was required for in vitro annealing and proper regulation by sRNAs and normal binding to long RNAs, such as the rpoS mRNA (19,26,27). Moreover, Hfq from Pseudomonas aeruginosa and Clostridium difficile, which have much shorter CTDs than E. coli Hfq, functionally replace E. coli Hfq for certain sRNA·mRNA pairs but not others (28,29).…”
mentioning
confidence: 95%